THE ROLE OF SELF-AWARENESS IN BUILDING PSYCHOLOGICAL RESILIENCE IN YOUNG WOMEN (E Global Congress, 2025)
This thesis explores the critical role of self-awareness in fostering psychological resilience among young women. Self-awareness—the ability to recognize and understand one’s emotions, thoughts, and behaviors—enables young women to manage stress, build emotional regulation, and maintain a stable sense of identity. Through internal reflection, self-compassion, and adaptive coping strategies, self-awareness enhances resilience in the face of societal pressures, mental health challenges, and personal transitions. Drawing on psychological theories and contemporary research, this study argues that cultivating self-awareness is essential for helping young women thrive in today’s complex world.